Thinking through silicon: Cables and servers as epistemic infrastructures. (June 2022) - Munn, Luke
Data centers and undersea cables allow information to be transmitted, stored, and processed. Yet, more than passively housing knowledge, information infrastructures actively shape knowledge. Infrastructures facilitate a certain use case, privileging some forms of knowledge while ignoring others. And infrastructures are material investments by states or corporations at a particular site, solidifying their knowledge-production, while marginalizing alternatives. These conditions are exemplified by two sites in Tseung Kwan O, Hong Kong. The TKO Express is a private undersea cable that offers its clients high-speed connectivity between financial centers, supporting the "fast knowledge" of finance and trading, while ignoring slower or more social forms of intelligence. The TKOIE industrial estate allocated land to a data center rather than a community center, prioritizing the production of corporate, proprietary knowledge over local and communal knowledge. The article reworks the concept of epistemic infrastructures to stress how such facilities influence what can be known and what remains unknown.